2005
DOI: 10.7863/jum.2005.24.9.1181
|View full text |Cite
|
Sign up to set email alerts
|

The Sonographic and Color Doppler Features of Retained Products of Conception

Abstract: Objective. The purpose of this study was to identify the sonographic features of retained products of conception (RPOCs). Methods. Cases of clinically suspected RPOCs referred for pelvic sonography between September 1994 and July 2001 were identified. Patient age, indication, gestational age at delivery, and days postpartum were recorded and sonographic findings were reviewed. Outcomes were determined from medical records and pathology reports. Results. One hundred sixty-three cases were identified. Indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
77
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 14 publications
11
77
1
Order By: Relevance
“…The endometrial vascularity was seen in all 15 cases of retained product of conception in this study, which was consistent with the studies of Kamaya, et al 1 and Durfee, et al 2 8.08% patients dropped their Hb by at least 2 gr/dL but only 1 of these had IEV. The authors hypothesised that the vascularity of the endometrium in the contexts of RPOC and SPPH may be explained on the basis of neoangiogenesis in that area.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The endometrial vascularity was seen in all 15 cases of retained product of conception in this study, which was consistent with the studies of Kamaya, et al 1 and Durfee, et al 2 8.08% patients dropped their Hb by at least 2 gr/dL but only 1 of these had IEV. The authors hypothesised that the vascularity of the endometrium in the contexts of RPOC and SPPH may be explained on the basis of neoangiogenesis in that area.…”
Section: Discussionsupporting
confidence: 92%
“…In the study of Kamaya, et al, 1 the incidence was much higher and the degree of vascularity was graded from 0 to 3. All patients in this study, who had IEV, had RPOC which is consistent with the study of Durfee, et al 2 Endometrial vascularity was significantly higher in pregnant patients with live births than in those who miscarried 3 …”
Section: Discussionsupporting
confidence: 92%
“…2 Color Doppler flow is detected in the endometrium more often when RPOC are present than in the absence of RPOC (75% versus 40%, respectively). 1 Durfee et al 1 observed that the presence of blood flow on color Doppler imaging was not helpful in distinguishing the presence or absence of retained products, although blood flow was seen somewhat more commonly in the endometrium with retained products than without. Some retained products may have minimal or very slow blood flow despite failure of complete separation at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Color Doppler flow is more often detected in the endometrium when RPOC are present (75%) than in the absence of RPOC (40%). 1 Complete hydatidiform mole presents as a complex intrauterine mass with multiple anechoic areas of varying sizes (ie, a \snowstorm" appearance). 4 The sonographic features of an arteriovenous malformation (AVM) are often indistinguishable from those seen in gestational trophoblastic disease (GTD) and residual trophoblastic tissue in spontaneous abortion.…”
mentioning
confidence: 99%
See 1 more Smart Citation